On optimization of resource allocation for LTE aided by WLAN networks with unlicensed frequency bands in internet of vehicles - Di Yao; Kai Zhang; Huaju Song; Sha Wei; Yuwen Qian; Jun Li (IET Communications)
Abstract Due to the explosive growth of communication devices and vehicles, the ever‐increasing communication data traffic is a challenge for mobile communication in the Internet of Vehicles (IoV). A practical solution is to offload the traffic from cellular networks to Wireless Local Area Network (WLAN), that is, WiFi, where the spectrum is license‐free. However, the coordination of unlicensed spectrum severely reduces the utilization rate on the spectrum. In this case, unlicensed networks assisted access is proposed to facilitate long‐term evolution technology in unlicensed spectrum (LTE‐U). To improve the data rate for LTE‐U and WLAN users, an allocation optimization scheme for the resources of the licensed and unlicensed spectrum is proposed. Accordingly, the data rate of LTE‐U users and WLAN users can be maximized by adjusting the transmit power and the frequency occupancy time ratio of the unlicensed spectrum for the small cell and WLAN users. Numerical results show that the proposed hybrid LTE networks with WLAN can improve the communication efficiency for the served users.